add [tex]\bf{\frac{1}{5}d }[/tex] on both sides.
[tex]\boldsymbol{\dfrac{4}{5}d+3+\dfrac{1}{5}d=-2 }[/tex]
combine [tex]\bf{\frac{4}{5}d }[/tex] and [tex]\bf{\frac{1}{5}d }[/tex] to get d.
[tex]\boldsymbol{d+3=-2}[/tex]
Subtract 3 from both sides.
[tex]\boldsymbol{d=-2-3}[/tex]
Subtract 3 from −2 to get −5.
[tex]\boxed{\boldsymbol{d=-5}} \ \ \to \ \ \bf{Answer}[/tex]
Verification
Let d=-5.
[tex]\sf{\dfrac{4}{5}\times-5+3=-2-\dfrac{1}{5}\times-5 }[/tex]
[tex]\rm{Apply \ this \ rule:\dfrac{a}{b}\times c=\dfrac{ac}{b} }[/tex]
[tex]\sf{\dfrac{4\times-5}{5}+3=-2-\dfrac{1}{5}\times-5 \ \ \to \ \ Multiply \ 4 \ by \ -5 }[/tex]
[tex]\sf{\dfrac{-20}{5}+3=-2-\dfrac{1}{5}\times-5 }[/tex]
[tex]\rm{Move \ the \ negative \ symbol \ to \ the \ left. }[/tex]
[tex]\sf{-\dfrac{20}{5}+3=-2-\dfrac{1}{5}\times-5 \ \ \to \ \ Simplify \ \frac{20}{5} \ to \ 4. }[/tex]
[tex]\sf{-4+3=-2- \dfrac{1}{5}\times-1 }[/tex]
[tex]\rm{Move \ the \ negative \ symbol \ to \ the \ left.}[/tex]
[tex]\sf{-4+3=-2-(-1) \ \ \to \ \ Simplify \ -4+3 \ to \ -1. }[/tex]
[tex]\sf{-1=-2-(-1) \ \ \to \ \ \to \ \ Remove \ parentheses. }[/tex]
[tex]\sf{-1=-2+1 \ \ \to \ \ Simplify \ -2+1 \ to \ -1.}[/tex]
[tex]\sf{-1=-1 \ \to \ Equality \ is \ met.}[/tex]
Checked ✅
[tex]\huge \red{\boxed{\green{\boxed{\boldsymbol{\purple{Pisces04}}}}}}[/tex]